2021
DOI: 10.1007/s10237-020-01413-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of left atrial ligation-driven altered inflow hemodynamics on embryonic heart development: clues for prenatal progression of hypoplastic left heart syndrome

Abstract: Congenital heart defects (CHDs) are abnormalities in the heart structure present at birth. One important condition is hypoplastic left heart syndrome (HLHS) where severely underdeveloped left ventricle (LV) cannot support systemic circulation. HLHS usually initiates as localized tissue malformations with no underlying genetic cause, suggesting that disturbed hemodynamics contribute to the embryonic development of these defects. Left atrial ligation (LAL) is a surgical procedure on embryonic chick resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 60 publications
0
33
0
2
Order By: Relevance
“…The same findings were presented recently, where Salman and colleagues conducted CFD analyses on LAL and control hearts and showed that LAL resulted in a decrease in the left AV canal WSS levels at two time points (pre-and post-septation). This reduction was persistent and was compensated by increased WSS in the right side of the hearts [33]. These sustained hemodynamic alterations following the surgery are thought to be the cause of the cardiac structural defects post LAL.…”
Section: Lal Induced Hemodynamic Alterationsmentioning
confidence: 98%
See 1 more Smart Citation
“…The same findings were presented recently, where Salman and colleagues conducted CFD analyses on LAL and control hearts and showed that LAL resulted in a decrease in the left AV canal WSS levels at two time points (pre-and post-septation). This reduction was persistent and was compensated by increased WSS in the right side of the hearts [33]. These sustained hemodynamic alterations following the surgery are thought to be the cause of the cardiac structural defects post LAL.…”
Section: Lal Induced Hemodynamic Alterationsmentioning
confidence: 98%
“…Cardiogenesis continues under constantly evolving hemodynamic environment [31]. Previous animal studies from our group and others have shown that surgical interference affecting hemodynamics induce clinically relevant cardiac defects [10,19,21,32,33].…”
Section: Mechanosensitive Cardiac Pathways In Embryonic Chickmentioning
confidence: 99%
“…Дифференциация эмбриональной сердечной трубки происходит на 3-й неделе после овуляции, а сердцебиение возникает к 4-й неделе [3]. К этому моменту фетоплацентарное кровообращение состоит из двух компонентов: один направлен к желточному мешку (желточное кровообращение), а другой к плаценте (кровообращение хориона) [4]. Желточное кровообращение формируется первым, и его функция является наиболее важной при развитии сердца плода.…”
Section: How Might It Impact On Clinical Practice In the Foreseeable ...unclassified
“…Нормальное развитие плаценты зависит от адекватной имплантации, иммунотолерантности матери, правильного формирования плацентарного ложа, достаточной оксигенации и обмена веществ через плаценту, который обеспечивается гемохориальной плацентацией. Для этого необходима соответствующая трансформация материнских спиральных артерий 4 Institute for Preventive and Social Medicine; 4 Corresponding author: Valentina I. Tsibizova, e-mail: tsibizova.v@gmail.com…”
Section: введение / Introductionunclassified
“…Disturbed hemodynamics has been suggested as an important factor for such cases ( Salman and Yalcin, 2021 ). Compared to healthy fetal hearts, the hemodynamic environment of HLHS hearts shows substantial differences due to the underdevelopment of the left heart ( Salman et al, 2021a ), which results in a significantly deteriorated life quality for the patients with HLHS ( Dempster et al, 2017 ). The blood flow in HLHS hearts is disturbed as a consequence of the developmental disorders.…”
Section: Introductionmentioning
confidence: 99%